Relações Raciais e Questão Social: contradições dialeticamente racializadas e radicalizadas - um improrrogável debate ao Serviço Social - Rodrigues, Cheliman Alves (2023)
The research has as main objective to investigate the space occupied by the discus-sion that emphasizes the racial issue as an essential element in its genesis and perpetuation of the social issue especially in the Brazilian context, in the training in Social Work. It recognizes that the social issue constitutes the object of work of so-cial workers and, therefore, must be understood in its entirety. In addition, the study argues that structural racism plays a fundamental role in maintaining the social is-sue in Brazil and that this social issue in Brazil is even more radicalized because it is racialized, being present in its foundations and manifestations. The research adopts a qualitative approach and uses both field research and literature review to deepen the discussion. In the field research component, the study involves a dia-logue with four Social Work professors, who, through semi-structured interviews, share their perceptions about the relationship between the social issue and the ra-cial issue in the training of new social workers. The fundamental objective is to en-rich the reflections on the interconnection between ethnic-racial issues and the so-cial issue, as well as to evaluate the relevance of this debate in the training of social workers